Hip muscle activity during 3 side-lying hip-strengthening exercises in distance runners - McBeth, J. M.; Earl-Boehm, J. E.; Cobb, S.C.; Huddleston, W. E. (Journal of Athletic Training, 2012)
Abstract: Context: Lower extremity overuse injuries are associated with gluteus medius (GMed) weakness. Understanding the activation of muscles about the hip during strengthening exercises is important for rehabilitation. Objective: To compare the electromyographic activity produced by the gluteus medius (GMed), tensor fascia latae (TFL), anterior hip flexors (AHF), and gluteus maximus (GMax) during 3 hip-strengthening exercises: hip abduction (ABD), hip abduction with external rotation (ABD-ER), and clamshell (CLAM) exercises. Design: Controlled laboratory study. Setting: Laboratory. Patients or Other Participants: Twenty healthy runners (9 men, 11 women; age = 25.45 ± 5.80 years, height = 1.71 ± 0.07 m, mass = 64.43 ± 7.75 kg) participated. Intervention(s): A weight equal to 5% body mass was affixed to the ankle for the ABD and ABD-ER exercises, and an equivalent load was affixed for the CLAM exercise. A pressure biofeedback unit was placed beneath the trunk to provide positional feedback. Main Outcome Measure(s): Surface electromyography (root mean square normalized to maximal voluntary isometric contraction) was recorded over the GMed, TFL, AHF, and GMax. Results: Three 1-way, repeated-measures analyses of variance indicated differences for muscle activity among the ABD (F3,57 = 25.903, P < .001), ABD-ER (F3,57 = 10.458, P < .001), and CLAM (F3,57 = 4.640, P = .006) exercises. For the ABD exercise, the GMed (70.1 ± 29.9%), TFL (54.3 ± 19.1%), and AHF (28.2 ± 21.5%) differed in muscle activity. The GMax (25.3 ± 24.6%) was less active than the GMed and TFL but was not different from the AHF. For the ABD-ER exercise, the TFL (70.9 ± 17.2%) was more active than the AHF (54.3 ± 24.8%), GMed (53.03 ± 28.4%), and GMax (31.7 ± 24.1%). For the CLAM exercise, the AHF (54.2 ± 25.2%) was more active than the TFL (34.4 ± 20.1%) and GMed (32.6 ± 16.9%) but was not different from the GMax (34.2 ± 24.8%). Conclusions: The ABD exercise is preferred if targeted activation of the GMed is a goal. Activation of the other muscles in the ABD-ER and CLAM exercises exceeded that of GMed, which might indicate the exercises are less appropriate when the primary goal is the GMed activation and strengthening.